NILAI AKHLAK DI MASA PANDEMI PERSPEKTIF HADITS - Debibik Nabilatul Fauziah (Taklim : Jurnal Pendidikan Agama Islam, 2022)
AbstactMoral is a crucial thing that must be owned by a Muslim in his life, including when a disaster strikes. The Prophet PUBH was sent to perfect noble character, there are many hadiths of the Prophet PUBH that discuss diseases or epidemics that are spread in various books of hadith, in this paper presented three authentic hadiths relating to disease and plague and the moral values contained therein. The moral values that are infused from the three hadiths include the character of grace, the character of patience, the character of justice, the character of ghafar and the character of gratitude. These five commendable morals when practiced by a Muslim means that he has imitated the attributes of Allah SWT.Keywords: Noble Character, Hadits, Islamic Values, Moral ValueAbstrakAkhlak adalah hal krusial yang harus dimiliki seorang muslim dalam kehidupannya termasuk saat tertimpa musibah. Nabi SAW diutus untuk menyempurnakan akhlak mulia, banyak hadits Nabi SAW yang membahas tentang penyakit ataupun wabah yang tersebar di berbagai kitab hadits, dalam tulisan ini dipaparkan tiga buah hadits shahih yang berkaitan dengan penyakit dan wabah serta nilai akhlak yang terkandung di dalamnya. Nilai akhlak yang diresapi dari ketiga hadits tersebut antara lain adalah akhlak rahmat, akhlak sabar, akhlak adil, akhlak ghafar dan akhlak syukur. Kelima akhlak terpuji ini apabila diamalkan seorang muslim berarti dia telah meneladani sifat-sifat Allah SWT.Kata Kunci: Akhlak, Hadits, Nilai-Nilai Islami, Nilai Moral